Implementing Permenpan Number 16/2009 About Guidance and Counseling Services in Primary School: Teachers’ Need Analysis - Hadiarni Hadiarni; Desri Jumiarti; Ardimen Ardimen; Wenda Asmita; Vio Litia Khairiah (Ta'dib, 2023)
The aim of this quantitative descriptive study is to describe the needs of primary school teachers in providing counseling services as the implementation Permenpan Number 16 of 2009, Permendiknas Number 35 of 2010 and POP BK SD. The population was primary school teachers throughout West Sumatera, totaling 129 people and were determined as the research sample. The data were collected by using questionnaire which assessed the obstacles faced by the teacher in the implementation of Guidance and Counseling, and the needs to overcome these obstacles. Scale measurement used the Guttman scale and distributed by using Google Form application. The research findings show that: 1) 96.9% of respondents had understood their responsibility to provide counseling services, 2) 86.8% had implemented counseling services. 3) The obstacles experienced in providing counseling services: a) lack of knowledge (61.2%). b) lack of skills in developing instruments (47.3%). c) lack of skills in processing instrument results (46.5%). d) lack of skills in implementing counseling services (48.1%) and e) lack of supporting infrastructure (66.7%). 4) The need to overcome the obstacles: a) increasing knowledge (71.3%), b) training in preparing need assessment instruments (58.1%), c) training in preparing counseling programs (58.9%) and d) skills training for providing counseling services (64.3%). It is expected that the findings of this study can be followed up by subsequent research so that the obstacles experienced by class teachers can be overcome and counseling services in primary schools can run optimally.